Designing Interface of Rhino Robot’S Operator Control Unit using Development Board LattePanda - Livian Tjandra; Achmad Affandi; Imam Arifin; M. Fajar Adityo (IPTEK Journal of Proceedings Series, 2019)
Rhino Robot work based on the control given by the user through a control device named Operator Control Unit (OCU). Currently, device that has been developed are form laptop toughbook with gamepad as controller. This design were inconvenience user, because there are batch of buttons which are not used to operate the robot. Moreover, using combination keys in gamepad to choose menu operation are required. Therefore, further development for the control device of Rhino Robot is do. The design were used is in OCU consist of an panel input that contains a several buttons and joystick which have a specific function to operate Rhino Robot. The buttons will be placed according to its function to the robot control process, using visualization of Rhino Robot to help user understanding the function of each buttons. This study will discuss the process to making interface of each buttons. In addition, it also discusses the process how to make an interface of LED which used to buttons indicator. The compilation process utilizes the existing LattePanda’s Arduino co-processor using Visual Studio to create a program. After testing of the several buttons using program that have been create, it is known that the program have been able to perform each function of buttons and LED in input panel.